Governments, labour, and the law in mid-Victorian Britain the trade union legislation of the 1870s - Curthoys, M. C. (Mark C.) (Oxford historical monographs., 2004)
In this publication, Mark Curthoys studies how governments and their specialist advisers, in an age of free trade and the minimal state, attempted to create a viable legal framework for trade unions and strikes.